The L-Total Graph of an L-Module. (17th October 2011) - Ebrahimi Atani Ebrahimi Atani, Reza Reza
Abstract : Let L be a complete lattice. We introduce and investigate the L -total graph of an L -module over an L -commutative ring. The main purpose of this paper is to extend the definition and results given in (Anderson and Badawi, 2008) to more generalize the L -total graph of an L -module case.